1998
DOI: 10.1021/cm970735b
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Study of the Surface Species Formed by Sequential Chemical Vapor Deposition of Dimethyl Zinc and Ethanethiol on Hydroxylated Alumina Surfaces

Abstract: The surface species formed by the reaction of gas-phase dimethylzinc with self-supported alumina pellets are examined by Fourier transform infrared spectroscopy. Dimethylzinc reacts with the surface −OH groups of alumina at room temperature evolving methane and yielding mainly surface Al−O−Zn−CH3 species. A small amount of CH3 species appears to bind to the Lewis acid sites of alumina as well, forming Al−CH3 groups. Temperature-dependence studies reveal that these species are stable at room temperature and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…A typical spectrum of methylzinc species remaining on the surface of the silica pellets after evacuation at room temperature is displayed in Figure . The C−H stretching modes at 2964 and 2916 cm -1 with a shoulder at 2852 cm -1 closely resemble the spectrum of the methylzinc surface species on alumina . Because of the very intense absorption by the silica Si−O lattice modes near and below 1300 cm -1 , the low-intensity bending modes of these methylzinc species, which appear at ∼1274 and ∼1180 cm -1 on alumina, are not observed on silica.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…A typical spectrum of methylzinc species remaining on the surface of the silica pellets after evacuation at room temperature is displayed in Figure . The C−H stretching modes at 2964 and 2916 cm -1 with a shoulder at 2852 cm -1 closely resemble the spectrum of the methylzinc surface species on alumina . Because of the very intense absorption by the silica Si−O lattice modes near and below 1300 cm -1 , the low-intensity bending modes of these methylzinc species, which appear at ∼1274 and ∼1180 cm -1 on alumina, are not observed on silica.…”
Section: Resultsmentioning
confidence: 67%
“…These readily hydrolyzed upon exposure to air or water . In a subsequent study, it was shown that the problem of hydrolysis could be eliminated by reacting the hydroxylated alumina surface with dimethylzinc (DMZ) and ethanethiol (EtSH). In the first step, the surface is covered mainly with the reactive methylzinc surface intermediates, which further react with ETSH to form surface thiolate species (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The water-stable (persistent) methyl groups, of which the C− H stretching mode is assigned to ∼2960 cm −1 in this work, may be bound to Al atoms in the lattice of alumina via Lewis acid−base interaction, rather than the Al atoms belonging to the overlayer of adsorbates (Scheme 1). 37,38 It is inferred that the temperature dependency of the persistent methyl groups observed in Figures 5 and 6 may be related to the methyl transfer reaction of Scheme 1. As aforementioned in the introduction section, the methyl transfer reaction occurs on a hydroxylated surface with a low OH coverage.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…These could be explained by the adsorption of organic species originating from pyrolysis of the by-products in Reaction , 1466 cm ±1 , 1576 cm ±1 ). [14,15] The absorption band at 1636 cm ±1 is probably due to physisorbed water, [15] and the signal at 1696 cm ±1 is due either to carbonyl, or C=C groups. The spectrum of the alumina powder collected at Position 2 is obviously a mixture of the spectra for alumina and polyethylene.…”
Section: Resultsmentioning
confidence: 99%